Settlement Patterns, Scheduling Conflicts, and Climate Variability: An Explanation for the Collapse of the Shivwits Ware Distribution Network. Issue 4 (2nd October 2019) - Willis, William M.; Harry, Karen G.
Abstract : During the middle Pueblo II period, a thriving ceramic distribution network linked the upland areas of northwestern Arizona with the lowland areas of southern Nevada. One kind of pottery transported through this network was Shivwits Ware, made on the southern end of the Shivwits Plateau, Arizona. Despite being located some 115 kilometers (70 mi) from the latter area, middle Pueblo II inhabitants of the Moapa Valley, Nevada, regularly acquired and used Shivwits Ware jars. By the late Pueblo II period, however, this ceramic distribution network had collapsed. This paper explores possible causes of the collapse by investigating changes in settlement patterns and landscape usage on the Shivwits Plateau. These data suggest that the collapse of the ceramic distribution network coincided with a shift in subsistence strategies triggered by climatic changes.